2016
DOI: 10.1016/j.geoforum.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Mobile activism, material imaginings, and the ethics of the edible: Framing political engagement through the Buycott app

Abstract: a b s t r a c tIn this article, we explore the discursive constructions of Buycott, a free mobile app that provides a platform for user-generated ethical consumption campaigns. Unlike other ethical consumption apps, Buycott's mode of knowledge production positions the app itself as neutral, with app users generating activist campaigns and providing both data and judgment. Although Buycott is not a dedicated food activism app, food features centrally in its campaigns, and the app seems to provide a mobile means… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 47 publications
0
28
0
Order By: Relevance
“…App users generate activist campaigns, and provide both data and judgment; other users join those campaigns. When a user scans a product with Buycott, the app alerts the user to conflicts between the campaigns the user has joined and the politics of the company behind the product (see also Eli et al, 2016). In our analysis of Buycott, we focused on consumer, app developer, and news media framings of Buycott's two largest campaigns (Eli et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…App users generate activist campaigns, and provide both data and judgment; other users join those campaigns. When a user scans a product with Buycott, the app alerts the user to conflicts between the campaigns the user has joined and the politics of the company behind the product (see also Eli et al, 2016). In our analysis of Buycott, we focused on consumer, app developer, and news media framings of Buycott's two largest campaigns (Eli et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…When a user scans a product with Buycott, the app alerts the user to conflicts between the campaigns the user has joined and the politics of the company behind the product (see also Eli et al, 2016). In our analysis of Buycott, we focused on consumer, app developer, and news media framings of Buycott's two largest campaigns (Eli et al, 2016). To obtain additional information about the operations of Buycott, Inc., the company behind the app, we conducted a brief Skype interview with company founder Ivan Pardo in February 2017.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has revealed how the promotion of 'food citizenship' through Good Guide, a system that ranks and grades products according to ethical criteria (Lyon 2014), relies on opaque metrics and an authoritative design, supplying norms that reproduce ethical consumerism as an individual act. Similarly, a study of the Buycott app (Eli 2016) argues that the app's design and the particular discursive and practical construction of ethical consumerism within the system shape representations of individual forms of ethical consumerism rather than supporting collective projects through interacting with the app (Eli 2016). Bringing issues of ethical consumption closer to the examination of information and communication technologies (ICTs), Gabriel and Lang (2015) argue that ICT has the potential to blur the definitional boundaries between consumers and producers and create new types of 'consuming work' (2015, p. 214), whereby acts of consumption expand to include not only procuring products but also generating and sharing product-related data.…”
mentioning
confidence: 99%
“…Although there exists a rich body of research about a plurality of choice prescribers and other market devices, this literature often lacks two important components for analysing ECAs. First, there is seldom any discussion about the particular material artefacts through which choice information is disseminated, and, secondly, the mechanisms of consumer acceptance or resistance towards devices are often missing from recent accounts of similar devices (Lekakis 2014, Hansson 2017, Eli 2016.…”
mentioning
confidence: 99%